Usefulness of voxel-based lesion mapping for predicting motor recovery in subjects with basal ganglia hemorrhage: A preliminary study with 2 case reports. Issue 23 (June 2016) - Kim, Dae Hyun; Kyeong, Sunghyon; Cho, Yoona; Jung, Tae-min; Ahn, Sung Jun; Park, Yoon Ghil
Abstract : Abstract: It is important to estimate motor recovery in the early phase after stroke. Many studies have demonstrated that both diffusion tensor tractography (DTT) and motor-evoked potentials (MEP) are valuable predictors of motor recovery, but these modalities do not directly reflect the status of the injured gray matter. We report on 2 subjects with basal ganglia hemorrhage who showed similar DTT and MEP findings, but had markedly different clinical outcomes. Specifically, Subject 1 showed no improvement in motor function, whereas Subject 2 exhibited substantial improvement 7 weeks after onset. To determine if differences in gray matter might lend insight into these different outcomes, we analyzed gray matter lesions of the 2 subjects using a novel voxel-based lesion mapping method. The lesion of Subject 1 mainly included the putamen, thalamus, and Heschl's gyri, indicating extension of the hemorrhage in the posterior direction. In contrast, the lesion of Subject 2 mainly included the putamen, insula, and pallidum, indicating that the hemorrhage extended anterior laterally. These differential findings suggest that voxel-based gray matter lesion mapping may help to predict differential motor recovery in subjects with basal ganglia hemorrhage with similar DTT and MEP findings.